Assessment of Technical Efficiency of Layer Production in Mampong Municipality: Stochastic Frontier Approach - N, Yenibehit; M, Murshed; M. J, Islam (Current Research in Agricultural Sciences, 2019)
This study used a Cobb-Douglas functional form of the stochastic production model to assess the technical efficiency of layer producers under commercial production system in the Mampong Municipality of Ghana. The study captures thirty (30) randomly selected layer poultry farms within the Asante Mampong enclave for the study. This study utilized the Maximum Likelihood Estimation (MLE) criteria to obtain farm specific technical efficiencies as well as their determinants of output and inefficiency. The study revealed that output was positively correlated to the number of birds, medication and quantity of water which all have significant coefficients at 5% and 10% levels of significance. The significant estimated gamma value of 0.99 implied that 99% of the total variation in layer output in the study area is due to the technical inefficiency. The study also showed that age, education, experience, extension contact, credit and type of poultry housing were related to socioeconomic characteristics influencing technical inefficiency. It is recommended for egg producers to observe the proper routine medication and add other supplementary drugs to boost the laying performance of their birds while intensifying stock size and increasing water usage to maximize production and close up the production gap. Poultry policies should consider motivating and increasing extension contact between extension agents and poultry farmers in the study area.